Reciclagem de cabos coaxiais e lâmpadas de LED aplicando operações de processamento mecânico - Martins, Thiago Rodrigues (2019)
Technological development, although linked to quality of life improvement, results in the increase of waste electrical and electronical equipment, which cables and LED bulbs are part of. Thus, new approaches towards recycling and recovery of these materials are of great need. This work deals with the applying of mechanical processing operations for the separation of materials from coaxial cables and LED bulbs. For the coaxial cables, the following steps were utilized: characterization, comminution, sieving, magnetic separation and electrostatic separation. A comparative between two processes was established: I – comminution, sieving and electrostatic separation; and II – comminution, magnetic separation and electrostatic separation. The analyzed parameters were: roll speed, electrostatic electrode distance, voltage applied to the electrodes and splitter angle. The best results for each process electrostatic separation were found at: I - roll speed of 30 rpm, electrostatic electrode distance of 8 cm, voltage applied to the electrodes of 30 kV and splitter angle of 0°; II – roll speed of 10 rpm, electrostatic electrode distance of 10 cm, voltage applied to the electrodes of 25 kV and splitter angle of 2,5. Process I obtained purity of 99,51% for aluminum and 96,79% for copper-clad steel, with recovery efficiency of 94,53% and 99,68%, respectively. Process II achieved purity of 99,53% (copper-clad steel) and 96,51% (aluminum), with recovery efficiency of 99,46% for the first and 70,12% for the latter. Due to the high values of purity and recovery attained, Process I was considered more advantageous for the recycling of coaxial cables. For the LED bulbs recycling, stages of characterization, comminution, sieving, electrostatic separation, magnetic separation and gravimetric separation were included. In the electrostatic separation the parameters of roll speed, voltage applied to the electrodes and splitter angle were evaluated, with the best values found at 20 rpm, 30 kV and 0°, respectively. In the magnetic separation, the roll speed was evaluated, with the best value found at 50 rpm. Magnetic separation was also adapted for the use of a conveyor belt for the separation according to the magnetic susceptibility of the materials. For the gravimetric separation, a solution of potassium iodide 30% was enough for the system separation. The proposed process enabled the obtention and separation of all LED bulb components with high purity and recovery efficiency, with total separation of the components in some steps.